2015
DOI: 10.3109/10715762.2015.1033416
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the oxidative damage of DNA, RNA, and their metabolites induced by hyperglycemia and related nephropathy in Sprague Dawley rats

Abstract: We used a sensitive and accurate method based on isotope dilution high-performance liquid chromatography-triple quadrupole mass spectrometry (ID-LC-MS/MS) to determine the levels of 8-oxo-7,8-dihydro-2-deoxyguanosine (8-oxo-dGsn) and 8-oxo-7,8-dihydroguanosin (8-oxo-Gsn) in various tissue specimens, plasma, and urine of hyperglycemic Sprague Dawley rats induced by streptozotocin (STZ). The oxidative DNA and RNA damages were observed in various organs and the amounts of 8-oxo-dGsn and 8-oxo-Gsn derived from DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…We also found that age had a significant effect on both 8-oxodGuo and 8-oxoGuo in the study subjects. This confirmed our previous research [ 18 , 19 ] and also the review by Jacob et al [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…We also found that age had a significant effect on both 8-oxodGuo and 8-oxoGuo in the study subjects. This confirmed our previous research [ 18 , 19 ] and also the review by Jacob et al [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Sex-stratified Cox models did not indicate any change in the results. diabetes is supported by evidence from animal models, and 8-oxoGuo has been found to be a more sensitive nucleic acid marker of diabetes morbidity and mortality than 8-oxodG (28). Moreover, a cross-sectional study indicated notably higher 8-oxoGuo levels in patients with type 2 diabetes with diabetic macrovascular complications, as well as higher 8-oxodG levels (although to a lesser extent) (29).…”
Section: Discussionmentioning
confidence: 90%
“…A further strength of this study is the method used for quantifying RNA oxidation. On oxidation, RNA is degraded and the oxidized nucleoside is excreted into urine, which can be assessed and interpreted to reflect intracellular disturbances in metabolism (28). The measurement of the oxidative modified nucleoside ensures that it does not originate from intestinal absorption, thus minimizing the contribution of diet and bacterial breakdown (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The results reported here are consistent with the hypothesis that these rapid changes in mRNA expressions result, at least in part, from damage to miRNAs and mRNAs by ROS which leads to perturbation of their interactions. It is not generally recognized that RNA is even more sensitive than DNA to oxidative damage [49]; the effects of ROS on RNA have been less explored, but in HeLa cells exposed to sub-milimolar concentrations of H 2 O 2 for 1 h, they led to a 50% decrease in the level of 8-oxoG in total RNA (reviewed in [50]). In our top-ranked miRNAs which seem to influence mRNA expressions most, the seed region is significantly enriched in GC; G has the lowest ionizing potential of the nucleic acid bases and G-specific damage by ROS is well documented for DNA and is therefore likely for RNA [51].…”
Section: Discussionmentioning
confidence: 99%